Introduction: A Scholarly Snapshot - Austin, Graeme W (Victoria University of Wellington Law Review, 2013)
Graeme W Austin, Associate Dean (Research) and Chair of Private Law, Introduces this 60th Anniversary edition of the Victoria University of Wellington Law Review. He provides a snapshot of a day in the life of the Victoria University of Wellington Law Faculty, focusing on the research activities of his colleagues, and reflects on what this might mean for the future of legal scholarship at Victoria.